Pyrolysis GC–MS as a rapid screening tool for determination of peat-forming plant composition in cores from ombrotrophic peat - McClymont, Erin L.; Bingham, Elizabeth M.; Nott, Chris J.; Chambers, Frank M.; Pancost, Richard D.; Evershed, Richard P. (Organic geochemistry, 2011)
► Analytical tool to rapidly screen peat archives to determine vegetation input explored. ► Confirmation of Sphagnum pyrolysate biomarker 4-isopropenylphenol (from sphagnum acid). ► Ratio of 4-isopropenylphenol and lignin (“I%”) tested as a Sphagnum macrofossil proxy. ► Macrofossil decay affects sphagnum acid; other markers quantify original sphagnum input. Peat cores provide decadal to centennial records of climatic and environmental change, including evidence for human/environment interaction. Existing palaeoenvironmental proxies (macrofossils, pollen, humification, testate amoebae, lipid composition) require multiple laboratory preparation steps and may be subject to differential preservation that can limit production of a continuous time series. The potential for pyrolysis gas-chromatography–mass-spectrometry (Py–GC–MS) to be applied to bulk peat samples is investigated here. The only preparatory step required was freeze drying. Analysis of a range of important peat-forming plants demonstrates that Sphagnum moss species are unique in containing the pyrolysis product of sphagnum acid, 4-isopropenylphenol. In contrast, non- Sphagnum species are rich in lignin pyrolysis products, which are absent from Sphagnum. The presence of these pyrolysis markers is reflected in bulk peat composition and tested here using archives from Bolton Fell Moss and Butterburn Flow (UK), Kontolanrahka (Finland) and Bissendorfer Moor (Germany). A ratio between 4-isopropenylphenol and two lignin pyrolysis products is proposed as a proxy for total Sphagnum input to peat archives and shows potential for use as a rapid screening tool for characterising bulk peat composition before more intensive analysis.